Effects of growth years on the quality of cultivated Bupleurum scorzonerifolium roots, with wild Bupleurum scorzonerifolium roots as a reference - Yuan, Changsheng; Zhou, Feng; Wang, Yihan; Li, Huaizhu; Li, Yongliang; Guan, Shan; Gao, Huaizhong; Gao, Shikong; Huang, Luqi; Liu, Yanmeng; Zhan, Zhilai (Frontiers in Plant Science, 2025)
IntroductionWith the rapid decline in wild Bupleurum scorzonerifolium (BSW) resources, large-scale planting of cultivated B. scorzonerifolium (BSC) has begun. However, the effects of growth years on the quality of BSC, as well as the quality difference between BSC and BSW remain unclear.MethodsThis study utilized trait characteristics, microstructure, cell wall components, sugar components, main pharmacological substances, metabolomics, and transcriptomics as key indicators and techniques, to comprehensively characterize and investigate the molecular mechanisms underlying the quality differences between BSC of different growth ages (1–3 years) and between BSC and BSW. Results and discussionAs the growth years increased, the root weight of BSC continuously increased, accompanied by root head expansion. Root length and middle and lower section diameters showed significant increases from 1 to 2 years, stabilizing from 2 to 3 years. The ratio of phloem width to xylem radius, along with the contents of total saponins and saikosaponins a, b2, c, and d, exhibited a trend of initial decrease, followed by an increase. Additionally, the number and size of oil cavities and ducts, as well as the volatile oil content, continuously increased. Metabolomic and transcriptomic analyses identified saponins and terpenoids as the primary differential components between different BSC growth years, with genes Bchns02G071080 and Bchns05G031860 (saponins) and Bchns01G03800 (terpenoids) identified as potential key regulatory genes. Furthermore, compared to the long-established, high-quality BSW, 3-year-old BSC (BSC3) showed the closest resemblance in morphological traits, microstructure, and chemical component content, particularly for key pharmacological substances, such as volatile oil, total saponins, and saikosaponins a, b2, c, and d. Considering both quality and economic benefits, BSC3 is recommended as a substitute for BSW. To the best of our knowledge, this is the first study to report the effects of growth years on the quality of BSC, offering valuable insights for guiding the artificial cultivation and quality assurance of B. scorzonerifolium.